Effectiveness and safety of monoclonal antibodies against amyloid-beta vis-à-vis placebo in mild or moderate Alzheimer's disease - Hao, Ying; Dong, Mingrui; Sun, Yingtong; Duan, Xiaohui; Niu, Wenquan (Frontiers in Neurology, 2023)
Backgrounds and objectives Currently, no consensus has been reached on the therapeutic implications of monoclonal antibodies against amyloid-beta (Aβ) in Alzheimer's disease (AD). This study aimed to examine the effectiveness and safety of monoclonal antibodies against Aβ as a whole and also to determine the superiority of individual antibodies vis-à-vis placebo in mild or moderate AD. Methods Literature retrieval, article selection, and data abstraction were performed independently and in duplicate. Cognition and function were appraised by the Mini-Mental State Examination (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog), Disability Assessment for Dementia (DAD), and Clinical Dementia Rating Scale-Sum of Boxes (CDR-SB). Effect sizes are expressed as standardized mean difference (SMD) with a 95% confidence interval (CI). Results Twenty-nine articles involving 108 drug-specific trials and 21,383 participants were eligible for synthesis. Of the four assessment scales, only CDR-SB was significantly reduced after using monoclonal antibodies against Aβ relative to placebo (SMD: −0.12; 95% CI: −0.2 to −0.03; p = 0.008). Egger's tests indicated a low likelihood of publication bias. At individual levels, bapineuzumab was associated with a significant increase in MMSE (SMD: 0.588; 95% CI: 0.226–0.95) and DAD (SMD: 0.919; 95% CI: 0.105–1.943), and a significant decrease in CDR-SB (SMD: −0.15; 95% CI: −0.282–0.018). Bapineuzumab can increase the significant risk of serious adverse events (OR: 1.281; 95% CI: 1.075–1.525). Conclusion Our findings indicate that monoclonal antibodies against Aβ can effectively improve instrumental activities of daily life in mild or moderate AD. In particular, bapineuzumab can improve cognition and function, as well as activities of daily life, and meanwhile, it triggers serious adverse events.